Coronary sinus thrombosis: insights from a comprehensive literature review - Chenlong Yi (Thrombosis Journal)
Abstract Coronary sinus thrombosis (CST) is a rare and severe disease that remains underrecognized in clinical practice. Most documented cases fall within the acute category, with non-specific symptoms, rapid progression, and a high mortality rate. In contrast, some cases follow an insidious course, leading to the formation of partial or incomplete thrombi that may not cause immediate death but can progress to severe complications over time. This review study the pathophysiology, clinical presentations, diagnostic challenges, and the association with persistent left superior vena cava (PLSVC), emphasizing the utility of imaging modalities such as Echocardiography, Computed Tomography, Magnetic Resonance Imaging and Venography. For management, anticoagulation remains the cornerstone of treatment for CST, with surgical thrombectomy reserved for severe or refractory cases. Post-treatment follow-up is highlighted as essential for monitoring recurrence and managing complications. In brief, the aim of this review is to enhance the understanding of CST and improve clinical outcomes through early recognition, tailored interventions, and multidisciplinary care.